1981
DOI: 10.1002/ar.1091990108
|View full text |Cite
|
Sign up to set email alerts
|

Development of seminal vesicles and coagulating glands in neonatal mice. I. The morphogenetic effects of various hormonal conditions

Abstract: Seminal vesicles (SV) and coagulating glands (CG) from neonatal mice 1- to 7-days old were observed in whole mount preparations. Untreated, normal SV developed elaborate epithelial branches beginning on day 3 with secondary branches appearing on day 6. Castration (C), estradiol treatment (E), and castration combined with estradiol treatment (C + E) inhibited the morphogenesis of the epithelial branches. Untreated CG formed solid epithelial stalks that developed lateral epithelial buds on day 3 which attained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…Indeed, it has been shown that androgen ablation of neonates delays but does not completely abrogate further growth (Donjacour and Cunha, 1988;Lung and Cunha, 1981;Price, 1936). Conversely, administration of exogenous androgens to sexually mature male rodents does not promote further growth and branching of the prostate (Berry and Isaacs, 1984).…”
Section: Mechanisms and Regulation Of Ductal Outgrowth And Branching mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that androgen ablation of neonates delays but does not completely abrogate further growth (Donjacour and Cunha, 1988;Lung and Cunha, 1981;Price, 1936). Conversely, administration of exogenous androgens to sexually mature male rodents does not promote further growth and branching of the prostate (Berry and Isaacs, 1984).…”
Section: Mechanisms and Regulation Of Ductal Outgrowth And Branching mentioning
confidence: 99%
“…The primitive urogenital sinus is then subdivided into the bladder at its rostral end, the urogenital sinus (UGS) in the middle, and the penile urethra caudally. The prostate forms through epithelial budding from the UGS starting at approximately 10 weeks of gestation in humans (Kellokumpu-Lehtinen et al, 1980), and at 17.5 dpc in the mouse (Bhatia-Gaur et al, 1999;Cunha et al, 1987;Lung and Cunha, 1981). Prostate organogenesis then continues under the influence of circulating androgens through birth and prepubertal stages, until the prostate reaches its mature size during puberty.…”
Section: Introductionmentioning
confidence: 99%
“…Main ducts are present in all lobes at birth, but lateral branching in the ventral prostates begins at birth (P1), the ante- rior prostate at P5, and the dorsolateral prostate by P10 (11,28). Gross examination of all three lobes of Klf6 f/f Nkx3.1…”
Section: Generation Of Mice Withmentioning
confidence: 99%
“…Canalization of the anterior prostate begins around P2 and progresses in a proximal to distal manner with elaboration of epithelial infolding or tufting within the luminal space (28,29). A novel ex vivo application of three-dimensional, high resolution ultrasound micro-imaging technology was employed to visualize the luminal space of intricately microdissected prostates.…”
Section: Generation Of Mice Withmentioning
confidence: 99%
“…The seminal vesicle arises as a hollow diverticulum of the lower Wolffian duct. During organogenesis the seminal vesicle undergoes a unique program of epithelial folding and branching morphogenesis to form a highly convoluted mucosa having crypt-like structures [Lung and Cunha, 1981]. The prostate arises from small solid epithelial buds that emerge from the urogenital sinus, elongate, and branch extensively in the surrounding mesenchyme.…”
Section: Discussionmentioning
confidence: 99%